Taxonomic update for giant viruses in the order Imitervirales (phylum Nucleocytoviricota) - Aylward, Frank O.; Abrahão, Jonatas S.; Brussaard, Corina P.D.; Fischer, Matthias G.; Moniruzzaman, Mohammad; Ogata, Hiroyuki; Suttle, Curtis A. (Archives of virology, 2023)
Large DNA viruses in the phylum Nucleocytoviricota , sometimes referred to as “giant viruses” owing to their large genomes and virions, have been the subject of burgeoning interest over the last decade. Here, we describe recently adopted taxonomic updates for giant viruses within the order Imitervirales. The families Allomimiviridae , Mesomimiviridae , and Schizomimiviridae have been created to accommodate the increasing diversity of mimivirus relatives that have sometimes been referred to in the literature as “extended Mimiviridae ”. In addition, the subfamilies Aliimimivirinae , Megamimivirinae, and Klosneuvirinae have been established to refer to subgroups of the Mimiviridae . Binomial names have also been adopted for all recognized species in the order. For example, Acanthamoeba polyphaga mimivirus is now classified in the species Mimivirus bradfordmassiliense .